Tensile, morphological and properties of soy protein isolate/nanohalloysite composite films - Tan, Boon Sheong (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
The effect of nanohalloysite (NH) content and its chemical modifications with methyl methacrylate (MMA) on the tensile properties, morphological, moisture content and enzymatic bidegradation of SPI/NH composite films were investigated. Composite films with different NH contents were prepared through solvent casting method. Glycerol were used as plasticizer in the composite films. The results showed that as the NH content increases, the tensile strength increased up to 10wt% of NH content and decreased with further increased in NH content. The increasing of NH content, the elongation at break decreased whereas the tensile modulus increased. The morphological study proved that the increasing of NH content showed poor interfacial interaction and dispersion of NH filler into SPI matrix. The SPI/NH composite films with higher NH content have higher moisture content and more resistance to enzymatic biodegradation. On the other hand, the tensile strength and tensile modulus of the treated SPI/NH composite films with MMA were higher than the untreated SPI/NH composite films. However, the elongation at break for treated composite films is lower compared to the untreated composite films. Furthermore, the treated composite films showed lower moisture content and better resistance to enzymatic biodegradation than the untreated composite films. MMA had enhanced the wettability and interfacial interaction, between SPI matrix and NH filler, as proven by morphological study. Also, the Fourier transform infrared (FTIR) results showed the presence of ester due to the esterification reaction occurred between NH with MAA.